A novel disease-causing NF1 variant in a Croatian family with neurofibromatosis type 1 - Gotovac Jerčić, Kristina (Array, 2019)
Neurofibromatosis type 1 (NF1) is the most common autosomal dominant neurocutaneous syndrome with the estimated prevalence ranging from 1 in 3000 to 1 in 4000 individuals and wide phenotypical variability. NF1 is caused by autosomal dominant heterozygous mutations in the neurofibromin gene which is located on the chromosome 17 (17q11.2). Phenotypically, NF1 patients have a very heterogeneous clinical phenotype. In this study, a novel frameshift NF1 variant was identified in a Croatian family with NF1 (mother and two daughters). The novel variant c. 4482_4483delTA leads to sequence change that creates a premature translational stop signal (p.His1494Glnfs*7) in the NF1 gene. Our study showed that even when the same germline NF1 variant has been identified, there is still huge phenotypic variability in patients even within the same family, and it makes prognosis of the disease more complex. The development of next-generation sequencing technologies which allow rapid and accurate identification of disease-causing mutations becomes crucial for molecular characterization of NF1 patients as well as for patient follow-up, in the context of genetic counseling and clinical management of patients.